Innocent Children in the Syrian Civil War - Çelikkaya, Mehmet Emin; Atıcı, Ahmet; EL, Çigdem; Akçora, Bülent (European Journal of Pediatric Surgery, 2020)
Introduction Our aim is to present the clinical and surgical characteristics of the children affected by the Syrian civil war.Materials and Methods Medical records were reviewed retrospectively for Syrian war victims between the ages of 0 and 18 who were brought to the emergency department of the Education and Research Hospital between March 2011 and March 2019. Each patient was evaluated with respect to demographic data (gender, age), type of injury, history of operations in Syria, injured organ(s), accompanying traumas and the mortality and trauma score.Results The majority of our study population of 147 patients were male (108/147, 73.46%), and 39 of the total were girls (26.53%). The mean age of the patients was 9 (7.5 ± 4). The mean age of the girls was 8.5 (range: 7 months to 16 years), and the mean age of the boys was 9.2 (4 months to 17 years). Seventeen patients who had abdominal surgery in Syria were operated on again after clinical and radiological observations. A total of 83 patients were operated on in Turkey. For 66 of those patients, the operation in Turkey was their first surgery on their war injuries. Seventeen patients were operated on in Syria but needed surgery again in Turkey.Conclusion War affects not only the battlefield, but also the neighboring countries in many aspects such as medical, social, and economic. Hollow organ injuries are the most common intraabdominal pathologies. Delayed intervention is associated with increase mortality and morbidity.
Keywords: Syrian civil war; pediatric trauma; battlefields